Intensive architectural survey of Byzantine rural settlements: a case study from the Mani - Pawlowski, Mark James (Journal of Greek Archaeology, 2020)
From data compiled through archaeological and architectural surveys, to excavated material and standing remains, the physical remains of the Peloponnese have been critical for the study of the Byzantine rural landscape. Important regional surveys such as the Nemea Valley Archaeological Project, the Pylos Regional Archaeological Project, and the Morea Project, to name just a few, have greatly increased our understanding and identification of Byzantine settlements and their use of the medieval landscape. However, there are few studies of complete medieval villages in the Peloponnese. This paper presents the architectural remains of a Byzantine village in the Mani peninsula, where the standing remains of settlements provide ample information about village planning, house forms, quarrying, agricultural practices, and even social relationships.